Recent Advances in mRNA-Based Vaccines Against Several Hepatitis Viruses - Rafid Jihad Albadr; Hayder Naji Sameer; Zainab H. Athab; Mohaned Adil; Ahmed Yaseen; Omer Qutaiba B. Allela (Biological Procedures Online)
Abstract Viral hepatitis is a significant danger to global public health as it is the primary cause of mortality worldwide. Hepatitis B virus (HBV), hepatitis C virus (HCV), and hepatitis D virus (HDV) are well-established infectious agents that significantly contribute to the development and transmission of hepatocellular carcinoma (HCC). Hepatitis E virus (HEV) is the pathogen responsible for acute viral hepatitis. 80% of liver malignancies are HCC, with HBV and HCV infections being the primary cause of seventy to eighty% of HCC cases. HEV may exacerbate liver inflammation and make other infections more severe. New vaccinations against the hepatitis virus are being developed to reduce the required doses for inducing an effective immune response and to help establish long-term protection in populations hyporesponsive to the vaccine. RNA-based vaccinations have emerged as a viable alternative. mRNA vaccines can help bridge the gap between the availability of effective vaccines and the rise of pandemic infectious diseases. Both human and animal studies have demonstrated that these vaccinations induce long-lasting and safe immunological responses. This review highlights the challenges faced in developing vaccines for the hepatitis virus, explicitly focusing on different vaccine candidates aimed at preventing or mitigating the illness. Here, we review the progress and comprehensive assessments of an mRNA-based vaccine designed to combat HAV, HBV, HCV, HDC, and HEV. Graphical Abstract